Analisis Etika Bisnis Digital Pada Sistem Dropshipping Affiliate Marketing Dan Live Selling Dalam Social Commerce - Azizah Nur Hidayati; Susi Susanti; Nelis Jamjam Munawaroh (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The rapid development of digital technology has given rise to the phenomenon of social commerce in Indonesia, marked by the emergence of dropshipping, affiliate marketing, and live selling business models. This study aims to analyze the compliance of these three business models with the principles of Islamic business ethics, particularly within the context of honesty (sidq), transparency (amanah), and the prohibition of harmful practices (gharar, tadlis). The research method employed is a comprehensive literature review using a descriptive qualitative approach, examining library sources that include reputable journals, fatwas of the National Sharia Board-Indonesian Ulema Council (DSN-MUI), and contemporary contemporary Islamic jurisprudence (fiqh muamalah) scholarly works. The results indicate that: (1) dropshipping potentially contains elements of gharar if the seller lacks clarity regarding product ownership; (2) affiliate marketing is permissible provided there is transparency in commissions and honesty in product information; (3) live selling is vulnerable to tadlis practices and impulsive buying pressure that can harm consumers. This study recommends the need for comprehensive Sharia-based ethical standards for social commerce platforms in Indonesia.